Implementation of Total Quality Management to Improve Management Quality at the Lembang Community Health Center - Nur Fadilah, Reutno; -, Wardana (Sekolah Tinggi Ilmu Kesehatan Sapta Bakti, 2024)
Puskesmas (Community Health Center) is a term used to describe health services provided to the community. Therefore, optimal performance is always required from Puskesmas in providing health services, making service quality a crucial issue. The purpose of this study was to determine the success of total quality management (TQM) implementation at the Lembang Community Health Center using a qualitative approach. Through in-depth interviews and observations, this study investigated how the Community Health Center implemented the TQM concept, the factors supporting it, and the obstacles they faced during the implementation process. The results highlighted the importance of leadership commitment, employee engagement, a supportive organizational culture, and a strong understanding of TQM principles for successful implementation. However, this study also identified several challenges such as lack of resources, resistance to change, and a lack of understanding of the TQM concept. This study provides valuable information for Community Health Center staff and healthcare practitioners in developing effective strategies to improve the quality of healthcare services through TQM implementation.